Treatment of cytomegalovirus retinitis with an intraocular sustained-release ganciclovir implant - C. Muccioli; R. Belfort Jr. (Brazilian Journal of Medical and Biological Research, 2000)
The objective of this prospective study was to evaluate the efficacy and complications of the use of an intraocular sustained-release ganciclovir implant for the treatment of active cytomegalovirus (CMV) retinitis in AIDS patients. Thirty-nine eyes of 26 patients were submitted to ocular surgery. All patients underwent complete ocular examination before and after surgery. The surgical procedure was always done under local anesthesia using the same technique. The mean time for the surgical procedure was 20 min (range, 15 to 30 min). The average follow-up period was 3.7 months. Of all patient, only 4 presented recurrence of retinitis after 8, 8, 9 and 2 months, respectively. Three of them received a successful second implant. All 39 eyes of the 26 patients presented healing of retinitis as shown by clinical improvement evaluated by indirect binocular ophthalmoscopy and retinography. Retinitis healed within a period of 4 to 6 weeks in all patients, with clinical regression signs from the third week on. Six (15.4%) eyes developed retinal detachment. None of the patients developed CMV retinitis in the contralateral eye. The intraocular implant proved to be effective in controlling the progression of retinitis for a period of up to 8 months even in patients for whom systemic therapy with either ganciclovir or foscarnet or both had failed. The intraocular sustained-release ganciclovir implant proved to be a safe new procedure for the treatment of CMV retinitis, avoiding the systemic side effects caused by the intravenous medications and improving the quality of life of the patients.